Russian expansion in Central Asia 1868-1873 Russia - Britain - Bukhara– Khiva)) (Journal of the College of Basic Education, 2026)
This research has explained the stages of Russia's expansion into Central Asia. Political, economic, and military factors converged in Russia's favor to implement its plan. Meanwhile, the Central Asian khanates suffered from the disintegration of their social and political structures. Russia was able to occupy Tashkent in 1865 and Kokand in 1866 and imposed a treaty on Bukhara on June 23, 1868, granting Russia extensive privileges. Russia's policy toward Central Asia in the first years after 1868 was to preserve the gains it had achieved in previous years. It supported Muzaffar al-Din, the ruler of Bukhara, in eliminating the rebels. British-Russian negotiations between 1869 and 1873 resulted in an agreement to demarcate the border between Bukhara and Afghanistan within a framework of mutual understanding. Both powers also committed to using their influence to ensure the protection of that border on both sides. In effect, each power implicitly recognized the other's sphere of influence. Russia decided to put an end to Khiva's traditional practices of encroaching on the Russian border, plundering caravans, and imposing duties on Russian merchants. It took control of the Krasnovodsk Bay on November 5, 1869, and then proceeded to subjugate the Khiva ruler through successful military operations, leading to the imposition of a treaty on August 12, 1873, which granted Russia significant privileges in Khiva. Russia later concluded a treaty with Bukhara on September 28, 1873. The new treaty confirmed the contents of the 1868 trade agreement, introducing changes favorable to Russia.